# ICSE Class 10 Maths Matrices Previous Years Questions Solution

This page consists of the solution to previous years questions from the chapter Matrices. ICSE Class 10 Maths Matrices Previous Years Questions Solution is going to be very beneficial for the students appearing for ICSE class 10 Board exam. The page contains solution to Matrices PYQs which came in ICSE Board exams from the year 2010 to 2023. You can also download the PDF of the questions from the chapter.

## ICSE Class 10 Maths Matrices Previous Years Questions Solution

$\style{font-size:12px}{1.\;If\;A=\begin{bmatrix}1&3\\2&4\end{bmatrix},\;B=\begin{bmatrix}1&2\\2&4\end{bmatrix},\;C=\begin{bmatrix}4&1\\1&5\end{bmatrix}\;and\;I=\begin{bmatrix}1&0\\0&1\end{bmatrix}\\find\;A(B+C)\;-\;14I.\;\;\;\lbrack2023\rbrack\\\\Step-by-step\;Explanation:\\(B+C)=\;\begin{bmatrix}1+4&2+1\\2+1&4+5\end{bmatrix}\\\;\;=\begin{bmatrix}5&3\\3&9\end{bmatrix}\\A(B+C)=\begin{bmatrix}1&3\\2&4\end{bmatrix}\;\begin{bmatrix}5&3\\3&9\end{bmatrix}\\\;\;=\begin{bmatrix}1\times5+3\times3&1\times3+3\times9\\2\times5+4\times3&2\times3+4\times9\end{bmatrix}\\\;\;=\begin{bmatrix}5+9&3+27\\10+12&6+36\end{bmatrix}\\\;\;=\begin{bmatrix}14&30\\22&42\end{bmatrix}\\A(B+C)\;-\;14I\\=\begin{bmatrix}14&30\\22&42\end{bmatrix}-14\begin{bmatrix}1&0\\0&1\end{bmatrix}\\=\begin{bmatrix}14&30\\22&42\end{bmatrix}-\begin{bmatrix}14&0\\0&14\end{bmatrix}\\=\begin{bmatrix}14-14&30-0\\22-0&42-14\end{bmatrix}\\=\begin{bmatrix}0&30\\22&28\end{bmatrix}\\}$

$\style{font-size:14px}{2.\;If\;\begin{bmatrix}2&0\\0&4\end{bmatrix}\;\begin{bmatrix}x\\y\end{bmatrix}=\begin{bmatrix}2\\-8\end{bmatrix},\;the\;value\;of\;x\;and\;y\;respectively\;are\\\\(a)\;1,\;-2\\(b)\;-2,\;1\\(c)\;1,\;2\\(d)\;-2,\;-1\;\;\;\;\lbrack2023\rbrack\\}$

Solution: (a)

Step-by-step Explanation:

$\style{font-size:14px}{\begin{bmatrix}2&0\\0&4\end{bmatrix}\;\begin{bmatrix}x\\y\end{bmatrix}=\begin{bmatrix}2\\-8\end{bmatrix}\\\begin{bmatrix}2\times x+0\times y\\0\times x+4\times y\end{bmatrix}=\begin{bmatrix}2\\-8\end{bmatrix}\\\begin{bmatrix}2x+0\\0+4y\end{bmatrix}=\begin{bmatrix}2\\-8\end{bmatrix}\\\begin{bmatrix}2x\\4y\end{bmatrix}=\begin{bmatrix}2\\-8\end{bmatrix}\\2x=2\;\;and\;4y=-8\\x=1\;\;\;\;\;\;\;\;\;\;y=-2}$

Watch the video solution of ICSE Class 10 Maths Matrices Previous Years Questions Solution Here.

$\style{font-size:14px}{3.\;If\;A=\begin{bmatrix}3&5\\1&4\end{bmatrix}\;,\;B=\begin{bmatrix}2&4\\0&3\end{bmatrix}\;and\;C=\begin{bmatrix}1&-1\\2&1\end{bmatrix},\\then\;5A-BC\;is\;equal\;to:\\(a)\;\begin{bmatrix}-5&-23\\1&17\end{bmatrix}\\(b)\;\begin{bmatrix}5&23\\1&17\end{bmatrix}\\(c)\;\begin{bmatrix}-2&8\\-3&3\end{bmatrix}\\(d)\;\begin{bmatrix}5&23\\-1&17\end{bmatrix}\;\;\;\lbrack2021\;semester-1\rbrack\\}$

Solution: (d)

Step-by-step Explanation:

$\style{font-size:14px}{5A-BC\\=5\begin{bmatrix}3&5\\1&4\end{bmatrix}-\begin{bmatrix}2&4\\0&3\end{bmatrix}\begin{bmatrix}1&-1\\2&1\end{bmatrix}\\=\begin{bmatrix}15&25\\5&20\end{bmatrix}-\begin{bmatrix}2\times1+4\times2&2(-1)+4\times1\\0\times1+3\times2&0(-1)+3\times1\end{bmatrix}\\=\begin{bmatrix}15&25\\5&20\end{bmatrix}-\begin{bmatrix}2+8&-2+4\\0+6&0+3\end{bmatrix}\\=\begin{bmatrix}15&25\\5&20\end{bmatrix}-\begin{bmatrix}10&2\\6&3\end{bmatrix}\\=\begin{bmatrix}15-10&25-2\\5-6&20-3\end{bmatrix}\\=\begin{bmatrix}5&23\\-1&17\end{bmatrix}\\}$

$\style{font-size:14px}{4.\;If\;A=\begin{bmatrix}5&10\\3&-4\end{bmatrix}\;and\;I=\begin{bmatrix}1&0\\0&1\end{bmatrix},\\then\;AI\;is\;equal\;to:\\(a)\;\begin{bmatrix}1&0\\0&1\end{bmatrix}\\(b)\;\begin{bmatrix}5&10\\-3&4\end{bmatrix}\\(c)\;\begin{bmatrix}5&10\\3&-4\end{bmatrix}\\(d)\;\begin{bmatrix}15&15\\-1&-1\end{bmatrix}\;\;\lbrack2021\;semester-1\rbrack\\}$

Solution: (c)

Step-by-step Explanation:

$\style{font-size:14px}{AI\;\\=\begin{bmatrix}5&10\\3&-4\end{bmatrix}\;\begin{bmatrix}1&0\\0&1\end{bmatrix}\\=\begin{bmatrix}5\times1+10\times0&5\times0+10\times1\\3\times1+(-4)\times0&3\times0+(-4)\times1\end{bmatrix}\\=\begin{bmatrix}5+0&0+10\\3+0&0-4\end{bmatrix}\\=\begin{bmatrix}5&10\\3&-4\end{bmatrix}}$

5. The product AB of two matrices A and B is possible if:

(a) A and B have the same number of rows.
(b) The number of columns of A is equal to the number of rows of B.
(c) The number of rows of A is equal to the number of columns of B.
(d) A and B have the same number of columns. [2021 Semester-I]

Solution: (b)The number of columns of A is equal to the number of rows of B.

ICSE Class 10 Maths PYQs Solution Chapter-wise

$6.\;If\;A=\begin{bmatrix}3&0\\5&1\end{bmatrix}\;and\;B=\begin{bmatrix}-4&2\\1&0\end{bmatrix},\\find\;A^2-2AB+B^2.\lbrack2020\rbrack\\$

Step-by-step Explanation:

$A^2=\begin{bmatrix}3&0\\5&1\end{bmatrix}\;\begin{bmatrix}3&0\\5&1\end{bmatrix}\;\\\;=\begin{bmatrix}3\times3+0\times5&3\times0+0\times1\\5\times3+1\times5&5\times0+1\times1\end{bmatrix}\;\\=\begin{bmatrix}9&0\\20&1\end{bmatrix}\;\\AB=\begin{bmatrix}3&0\\5&1\end{bmatrix}\;\begin{bmatrix}-4&2\\1&0\end{bmatrix}\\\;=\begin{bmatrix}3(-4)+0\times1&3\times2+0\times0\\5(-4)+1\times1&5\times2+1\times0\end{bmatrix}\\\;=\begin{bmatrix}-12&6\\-19&10\end{bmatrix}\\B^2=\begin{bmatrix}-4&2\\1&0\end{bmatrix}\begin{bmatrix}-4&2\\1&0\end{bmatrix}\\\;=\begin{bmatrix}(-4)(-4)+2\times1&(-4)\times2+2\times0\\1(-4)+0\times1&1\times2+0\times0\end{bmatrix}\\\;=\begin{bmatrix}18&-8\\-4&2\end{bmatrix}\\Hence,\;A^2-2AB+B^2\\=\begin{bmatrix}9&0\\20&1\end{bmatrix}\;-2\begin{bmatrix}-12&6\\-19&10\end{bmatrix}+\begin{bmatrix}18&-8\\-4&2\end{bmatrix}\\=\begin{bmatrix}9&0\\20&1\end{bmatrix}\;-\begin{bmatrix}-24&12\\-38&20\end{bmatrix}\;+\begin{bmatrix}18&-8\\-4&2\end{bmatrix}\\=\begin{bmatrix}9+24+18&0-12-8\\20+38-4&1-20+2\end{bmatrix}\\=\begin{bmatrix}51&-20\\54&-17\end{bmatrix}$

$\style{font-size:14px}{7.\;Given,\;A=\begin{bmatrix}x&3\\y&3\end{bmatrix}.\;If\;A^2=3I,\;\;\;\lbrack2020\rbrack\\where\;I\;is\;identity\;matrix\;of\;order\;2,\;find\;x\;and\;y.\\}$

Solution: x= -3, y= -2

Step-by-step Explanation:

$\style{font-size:14px}{A^2=3I\\\begin{bmatrix}x&3\\y&3\end{bmatrix}\begin{bmatrix}x&3\\y&3\end{bmatrix}=3\begin{bmatrix}1&0\\0&1\end{bmatrix}\\\begin{bmatrix}x^2+3y&3x+9\\xy+3y&3y+9\end{bmatrix}=\begin{bmatrix}3&0\\0&3\end{bmatrix}\\\therefore3x+9=0\\\Rightarrow3x=-9\\\Rightarrow x=-3\\and\;3y+9=3\\\Rightarrow3y=-6\\\Rightarrow y=-2\\\\}$

$\style{font-size:14px}{8.\;Simplify:\\\sin A\begin{bmatrix}\sin A&-\cos A\\\cos A&\sin A\end{bmatrix}+\cos A\begin{bmatrix}\cos A&\sin A\\-\sin A&\cos A\end{bmatrix}\;\;\lbrack2019\rbrack\\\\\\}$

Step-by-step Explanation:

$\style{font-size:14px}{\sin A\begin{bmatrix}\sin A&-\cos A\\\cos A&\sin A\end{bmatrix}+\cos A\begin{bmatrix}\cos A&\sin A\\-\sin A&\cos A\end{bmatrix}\;\\\\\begin{bmatrix}\sin^2A&-\sin A.\cos A\\\sin A.\cos A&\sin^2A\end{bmatrix}+\begin{bmatrix}\cos^2A&\sin A.\cos A\\-\sin A.\cos A&\cos^2A\end{bmatrix}\;\\\\\begin{bmatrix}\sin^2A+\mathrm{co}^2sA&-\sin A.\cos A+\sin A.\cos A\\\sin A.\cos A-\sin A.\cos A&\sin^2A+\cos^2A\end{bmatrix}\\\begin{bmatrix}1&0\\0&1\end{bmatrix}\\}$

$\style{font-size:14px}{9.\;Given,\begin{bmatrix}4&2\\-1&1\end{bmatrix}\times M=6I,\;where\;M\;is\;a\;matrix\;and\\I\;is\;unit\;matrix\;of\;order\;2\times2.\\(i)\;State\;the\;order\;of\;matrix\;M.\\(ii)\;Find\;the\;matrix\;M.\;\;\;\;\lbrack2019\rbrack\\}$

Step-by-step Explanation:

$\style{font-size:14px}{(i)\;(m\times n)(n\times p)=(m\times p)\\\Rightarrow(2\times2)(n\times p)=(2\times2)\\\Rightarrow order\;of\;matrix\;M=\;(2\times2)\\\\(ii)\;Let\;M=\begin{bmatrix}a&b\\c&d\end{bmatrix}\\\begin{bmatrix}4&2\\-1&1\end{bmatrix}\times M=6I\\\begin{bmatrix}4&2\\-1&1\end{bmatrix}\begin{bmatrix}a&b\\c&d\end{bmatrix}=6\begin{bmatrix}1&0\\0&1\end{bmatrix}\\\begin{bmatrix}4a+2c&4b+2d\\-a+c&-b+d\end{bmatrix}=\begin{bmatrix}6&0\\0&6\end{bmatrix}\\\therefore4a+2c=6\;…(i)\\-a+c=0\;….(ii)\\Multiplying\;(ii)\;by\;4\;and\;adding\;(i)\;and\;(ii)\\\begin{array}{r}4a+2c=6\\+-4a+4c=0\\\hline6c=6\end{array}\;\\\therefore\boldsymbol\;\boldsymbol c\boldsymbol=\mathbf1\\Putting\;c=1\;in\;(ii)\\-a+1=0\\\boldsymbol a\boldsymbol=\mathbf1\\Now,\\4b+2d=0\;…(iii)\\-b+d=6\;…(iv)\\Multiplying\;(iv)\;by\;4\;and\;adding\;(iii)\;and\;(iv)\\\begin{array}{r}4b+2d=0\\+-4b+4d=24\\\hline6d=24\end{array}\\\boldsymbol d\boldsymbol=\mathbf4\\Putting\;d=4\;in\;(iv)\\-b+4=6\\\boldsymbol b\boldsymbol=\boldsymbol-\mathbf2\\\boldsymbol M\boldsymbol=\mathbf{\left[\begin{array}{cc}1&-2\\1&4\end{array}\right]}\\}$

$\style{font-size:14px}{10.\;Find\;the\;value\;of\;’x’\;and\;’y’\;if:\\2\begin{bmatrix}x&7\\9&y-5\end{bmatrix}+\begin{bmatrix}6&-7\\4&5\end{bmatrix}=\begin{bmatrix}10&7\\22&15\end{bmatrix}\\}$

Solution: x= 2 and y= 10

Step-by-step Explanation:

$\style{font-size:14px}{2\begin{bmatrix}x&7\\9&y-5\end{bmatrix}+\begin{bmatrix}6&-7\\4&5\end{bmatrix}=\begin{bmatrix}10&7\\22&15\end{bmatrix}\\\\\begin{bmatrix}2x&14\\18&2y-10\end{bmatrix}+\begin{bmatrix}6&-7\\4&5\end{bmatrix}=\begin{bmatrix}10&7\\22&15\end{bmatrix}\\\begin{bmatrix}2x+6&14-7\\18+4&2y-10+5\end{bmatrix}=\begin{bmatrix}10&7\\22&15\end{bmatrix}\\\begin{bmatrix}2x+6&7\\22&2y-5\end{bmatrix}=\begin{bmatrix}10&7\\22&15\end{bmatrix}\\2x+6=10\;and\;2y-5=15\\\boldsymbol x\boldsymbol=\mathbf2\boldsymbol\;\boldsymbol a\boldsymbol n\boldsymbol d\boldsymbol\;\boldsymbol y\boldsymbol=\mathbf10}$

$\style{font-size:14px}{11.\;A=\begin{bmatrix}2&3\\5&7\end{bmatrix},\;B=\begin{bmatrix}0&4\\-1&7\end{bmatrix},\;C=\begin{bmatrix}1&0\\-1&4\end{bmatrix},\\find\;AC+B^2-10C.\;\;\lbrack2018\rbrack}$

Step-by-step Explanation:

$\style{font-size:14px}{\\AC=\begin{bmatrix}2&3\\5&7\end{bmatrix}\begin{bmatrix}1&0\\-1&4\end{bmatrix}\\\begin{bmatrix}2\times1+3(-1)&2\times0+3\times4\\5\times1+7(-1)&5\times0+7\times4\end{bmatrix}\\\begin{bmatrix}-1&12\\-2&28\end{bmatrix}\\B^2=\begin{bmatrix}0&4\\-1&7\end{bmatrix}\begin{bmatrix}0&4\\-1&7\end{bmatrix}\\\begin{bmatrix}0\times0+4(-1)&0\times4+4\times7\\(-1)\times0+7(-1)&(-1)\times4+7\times7\end{bmatrix}\\\begin{bmatrix}-4&28\\-7&45\end{bmatrix}\\AC+B^2-10C\\=\begin{bmatrix}-1&12\\-2&28\end{bmatrix}+\begin{bmatrix}-4&28\\-7&45\end{bmatrix}-10\begin{bmatrix}1&0\\-1&4\end{bmatrix}\\=\begin{bmatrix}-1&12\\-2&28\end{bmatrix}+\begin{bmatrix}-4&28\\-7&45\end{bmatrix}-\begin{bmatrix}10&0\\-10&40\end{bmatrix}\\=\begin{bmatrix}-1-4-10&12+28-0\\-2-7+10&28+45-40\end{bmatrix}\\=\begin{bmatrix}-15&40\\1&33\end{bmatrix}}$

$\style{font-size:14px}{12.\;If\;A=\begin{bmatrix}1&3\\3&4\end{bmatrix}\;and\;B=\begin{bmatrix}-2&1\\-3&2\end{bmatrix}\;and\;A^2-5B^2=5C,\\Find\;matrix\;C\;where\;C\;is\;a\;2\;by\;2\;matrix.\;\;\lbrack2017\rbrack}$

Step-by-step Explanation:

$\style{font-size:14px}{\\Let\;C=\begin{bmatrix}a&b\\c&d\end{bmatrix}\\A^2=\begin{bmatrix}1&3\\3&4\end{bmatrix}\begin{bmatrix}1&3\\3&4\end{bmatrix}\\\begin{bmatrix}1\times1+3\times3&1\times3+3\times4\\3\times1+4\times3&3\times3+4\times4\end{bmatrix}\\\begin{bmatrix}10&15\\15&25\end{bmatrix}\\B^2=\begin{bmatrix}-2&1\\-3&2\end{bmatrix}\;\begin{bmatrix}-2&1\\-3&2\end{bmatrix}\;\\\begin{bmatrix}(-2)(-2)+1(-3)&(-2)1+1\times2\\(-3)(-2)+2(-3)&(-3)1+2\times2\end{bmatrix}\;\\\begin{bmatrix}1&0\\0&1\end{bmatrix}\;\\A^2-5B^2=5C\\\begin{bmatrix}10&15\\15&25\end{bmatrix}-5\begin{bmatrix}1&0\\0&1\end{bmatrix}=5\begin{bmatrix}a&b\\c&d\end{bmatrix}\\\begin{bmatrix}10&15\\15&25\end{bmatrix}-\begin{bmatrix}5&0\\0&5\end{bmatrix}=\begin{bmatrix}5a&5b\\5c&5d\end{bmatrix}\\\begin{bmatrix}10-5&15-0\\15-0&25-5\end{bmatrix}=\begin{bmatrix}5a&5b\\5c&5d\end{bmatrix}\\\begin{bmatrix}5&15\\15&20\end{bmatrix}=\begin{bmatrix}5a&5b\\5c&5d\end{bmatrix}\\5a=5\\a=1\\5b=15\\b=3\\5c=15\\c=3\\5d=20\\d=4\\\boldsymbol m\boldsymbol a\boldsymbol t\boldsymbol r\boldsymbol i\boldsymbol x\boldsymbol\;\boldsymbol C\boldsymbol=\mathbf{\left[\begin{array}{cc}1&3\\3&4\end{array}\right]}}$

$13.\;Given\;matrix\;B=\begin{bmatrix}1&1\\8&3\end{bmatrix}.\\Find\;matrix\;X\;if\;X=B^2-4B.\\Hence,\;solve\;for\;a\;and\;b,\;given\;X\begin{bmatrix}a\\b\end{bmatrix}=\begin{bmatrix}5\\50\end{bmatrix}\;\lbrack2017\rbrack$

Step-by-step Explanation:

$\style{font-size:14px}{X=B^2-4B\\X=\begin{bmatrix}1&1\\8&3\end{bmatrix}\begin{bmatrix}1&1\\8&3\end{bmatrix}-4\begin{bmatrix}1&1\\8&3\end{bmatrix}\\X=\begin{bmatrix}1\times1+1\times8&1\times1+1\times3\\8\times1+3\times8&8\times1+3\times3\end{bmatrix}-\begin{bmatrix}4&4\\32&12\end{bmatrix}\\X=\begin{bmatrix}9&4\\32&17\end{bmatrix}-\begin{bmatrix}4&4\\32&12\end{bmatrix}\\X=\begin{bmatrix}9-4&4-4\\32-32&17-12\end{bmatrix}\\\boldsymbol X\boldsymbol=\mathbf{\left[\begin{array}{cc}5&0\\0&5\end{array}\right]}\\Now,\;X\begin{bmatrix}a\\b\end{bmatrix}=\begin{bmatrix}5\\50\end{bmatrix}\\\begin{bmatrix}5&0\\0&5\end{bmatrix}\begin{bmatrix}a\\b\end{bmatrix}=\begin{bmatrix}5\\50\end{bmatrix}\\\begin{bmatrix}5a\\5b\end{bmatrix}=\begin{bmatrix}5\\50\end{bmatrix}\\5a=5\;and\;5b=50\\\boldsymbol a\boldsymbol=\mathbf1\boldsymbol\;\boldsymbol a\boldsymbol n\boldsymbol d\boldsymbol\;\boldsymbol b\boldsymbol=\mathbf{10}}$

$\style{font-size:14px}{14.\;Given\;A=\begin{bmatrix}2&0\\-1&7\end{bmatrix}\;and\;I=\begin{bmatrix}1&0\\0&1\end{bmatrix}\\and\;A^2=9A+mI.\;Find\;m.\;\;\lbrack2016\rbrack}$

Solution: m= -14

Sep-by-step Explanation:

$\style{font-size:14px}{A^2=9A+mI\\\begin{bmatrix}2&0\\-1&7\end{bmatrix}\begin{bmatrix}2&0\\-1&7\end{bmatrix}=9\begin{bmatrix}2&0\\-1&7\end{bmatrix}+m\begin{bmatrix}1&0\\0&1\end{bmatrix}\\\begin{bmatrix}2\times2+0(-1)&2\times0+0\times7\\(-1)\times2+7(-1)&(-1)0+7\times7\end{bmatrix}=\begin{bmatrix}18&0\\-9&63\end{bmatrix}+\begin{bmatrix}m&0\\0&m\end{bmatrix}\\\begin{bmatrix}4&0\\-9&49\end{bmatrix}=\begin{bmatrix}18+m&0\\-9&63+m\end{bmatrix}\\18+m=4\\\Rightarrow\boldsymbol m\boldsymbol=\boldsymbol-\mathbf{14}\\}$

$\style{font-size:14px}{15.\;Given\;matrix\;A=\begin{bmatrix}4\sin30^\circ&\cos0^\circ\\\cos0^\circ&4\sin30^\circ\end{bmatrix}\;and\;B=\begin{bmatrix}4\\5\end{bmatrix},\\If\;AX=B\\(i)\;write\;the\;order\;of\;matrix\;X.\\(ii)\;Find\;the\;matrix\;’X’.\;\;\lbrack2016\rbrack}$

Step-by-step Explanation:

$\style{font-size:14px}{(i)\;(m\times n)(n\times p)=(m\times p)\\(2\times2)(n\times p)=(2\times1)\\\therefore\;Order\;of\;matrix\;X=(2\times1)\\(ii)\;Let\;X=\begin{bmatrix}a\\b\end{bmatrix}\\AX=B\\\begin{bmatrix}4\sin30^\circ&\cos0^\circ\\\cos0^\circ&4\sin30^\circ\end{bmatrix}\begin{bmatrix}a\\b\end{bmatrix}=\begin{bmatrix}4\\5\end{bmatrix}\\\begin{bmatrix}4\times\frac12&1\\1&4\times\frac12\end{bmatrix}\begin{bmatrix}a\\b\end{bmatrix}=\begin{bmatrix}4\\5\end{bmatrix}\\\begin{bmatrix}2&1\\1&2\end{bmatrix}\begin{bmatrix}a\\b\end{bmatrix}=\begin{bmatrix}4\\5\end{bmatrix}\\\begin{bmatrix}2a+b\\a+2b\end{bmatrix}=\begin{bmatrix}4\\5\end{bmatrix}\\2a+b=4\;…(1\}\\a+2b=5\;…(2)\\multiplying\;(2)\;by\;2\;and\;subtracting\;it\;from\;(1)\\\begin{array}{r}2a+b=4\\2a+4b=10\\\hline-3b=-6\end{array}\\b=2\\Putting\;b=2\;in\;(1)\\2a+2=4\\a=1\\\therefore Matrix\;X=\begin{bmatrix}1\\2\end{bmatrix}}$

$\style{font-size:14px}{16.\;If\;A=\begin{bmatrix}3&x\\0&1\end{bmatrix}\;and\;B=\begin{bmatrix}9&16\\0&-y\end{bmatrix},\\find\;x\;and\;y\;when\;A^2=B.\;\;\lbrack2015\rbrack}$

Solution: x = 4 and y = -1

Step-by-step Explanation:

$\style{font-size:14px}{A^2=B\\\begin{bmatrix}3&x\\0&1\end{bmatrix}\begin{bmatrix}3&x\\0&1\end{bmatrix}=\begin{bmatrix}9&16\\0&-y\end{bmatrix}\\\begin{bmatrix}3\times3+x\times0&3\times x+x\times1\\0\times3+1\times0&0\times x+1\times1\end{bmatrix}=\begin{bmatrix}9&16\\0&-y\end{bmatrix}\\\begin{bmatrix}9&4x\\0&1\end{bmatrix}=\begin{bmatrix}9&16\\0&-y\end{bmatrix}\\4x=16\;and\;1=-y\\\boldsymbol x\boldsymbol=\mathbf4\boldsymbol\;\boldsymbol a\boldsymbol n\boldsymbol d\boldsymbol\;\boldsymbol y\boldsymbol=\boldsymbol-\mathbf1}$

$\style{font-size:14px}{17.\;If\;A=\begin{bmatrix}3&7\\2&4\end{bmatrix},\;B=\begin{bmatrix}0&2\\5&3\end{bmatrix},\;C=\begin{bmatrix}1&-5\\-4&6\end{bmatrix},\\find\;AB-5C.\;\;\lbrack2015\rbrack\\}$

Step-by-step Explanation:

$\style{font-size:14px}{\\AB-5C\\\begin{bmatrix}3&7\\2&4\end{bmatrix}\;\begin{bmatrix}0&2\\5&3\end{bmatrix}-5\begin{bmatrix}1&-5\\-4&6\end{bmatrix}\\\begin{bmatrix}3\times0+7\times5&3\times2+7\times3\\2\times0+4\times5&2\times2+4\times3\end{bmatrix}-\begin{bmatrix}5&-25\\-20&30\end{bmatrix}\\\begin{bmatrix}35&27\\20&16\end{bmatrix}-\begin{bmatrix}5&-25\\-20&30\end{bmatrix}\\\begin{bmatrix}35-5&27+25\\20+20&16-30\end{bmatrix}\\\begin{bmatrix}30&52\\40&-14\end{bmatrix}}$

$\style{font-size:14px}{18.\;Find\;x,\;y\;if\;\begin{bmatrix}-2&0\\3&1\end{bmatrix}\;\begin{bmatrix}-1\\2x\end{bmatrix}+3\begin{bmatrix}-2\\1\end{bmatrix}=2\begin{bmatrix}y\\3\end{bmatrix}\;\;\lbrack2014\rbrack\\}$

Solution: x= 3 , y= -2

Step-by-step Explanation:

$\style{font-size:14px}{\begin{bmatrix}-2&0\\3&1\end{bmatrix}\;\begin{bmatrix}-1\\2x\end{bmatrix}+3\begin{bmatrix}-2\\1\end{bmatrix}=2\begin{bmatrix}y\\3\end{bmatrix}\\\begin{bmatrix}(-2)(-1)+0\times2x\\3(-1)+1\times2x\end{bmatrix}+\begin{bmatrix}-6\\3\end{bmatrix}=\begin{bmatrix}2y\\6\end{bmatrix}\\\begin{bmatrix}2\\-3+2x\end{bmatrix}+\begin{bmatrix}-6\\3\end{bmatrix}=\begin{bmatrix}2y\\6\end{bmatrix}\\\begin{bmatrix}2-6\\-3+2x+3\end{bmatrix}=\begin{bmatrix}2y\\6\end{bmatrix}\\\begin{bmatrix}-4\\2x\end{bmatrix}=\begin{bmatrix}2y\\6\end{bmatrix}\\-4=2y\;and\;2x=6\\\boldsymbol y\boldsymbol=\boldsymbol-\mathbf2\boldsymbol\;\boldsymbol a\boldsymbol n\boldsymbol d\boldsymbol\;\boldsymbol x\boldsymbol=\mathbf3\\}$

$19.\;Let\;A=\begin{bmatrix}2&1\\0&-2\end{bmatrix},\;B=\begin{bmatrix}4&1\\-3&-2\end{bmatrix}and\;C=\begin{bmatrix}-3&2\\-1&4\end{bmatrix}.\\Find\;A^2+AC-5B.\;\;\lbrack2014\rbrack$

Step-by-step Explanation:

$\style{font-size:14px}{\\A^2=\begin{bmatrix}2&1\\0&-2\end{bmatrix}\begin{bmatrix}2&1\\0&-2\end{bmatrix}\\=\begin{bmatrix}2\times2+1\times0&2\times1+1(-2)\\0\times2+(-2)\times0&0\times1+(-2)(-2)\end{bmatrix}\\=\begin{bmatrix}4&0\\0&4\end{bmatrix}\\AC=\begin{bmatrix}2&1\\0&-2\end{bmatrix}\begin{bmatrix}-3&2\\-1&4\end{bmatrix}\\=\begin{bmatrix}2(-3)+1(-1)&2\times2+1\times4\\0(-3)+(-2)(-1)&0\times2+(-2)4\end{bmatrix}\\=\begin{bmatrix}-7&8\\2&-8\end{bmatrix}\\A^2+AC-5B\\=\begin{bmatrix}4&0\\0&4\end{bmatrix}+\begin{bmatrix}-7&8\\2&-8\end{bmatrix}-5\begin{bmatrix}4&1\\-3&-2\end{bmatrix}\\=\begin{bmatrix}4&0\\0&4\end{bmatrix}+\begin{bmatrix}-7&8\\2&-8\end{bmatrix}-\begin{bmatrix}20&5\\-15&-10\end{bmatrix}\\=\begin{bmatrix}4-7-20&0+8-5\\0+2+15&4-8+10\end{bmatrix}\\=\mathbf{\left[\begin{array}{cc}-23&3\\17&6\end{array}\right]}}$

$\style{font-size:14px}{20.\;A=\begin{bmatrix}2&-6\\2&0\end{bmatrix},\;B=\begin{bmatrix}-3&2\\4&0\end{bmatrix},\;C=\begin{bmatrix}4&0\\0&2\end{bmatrix}.\\Find\;the\;matrix\;X\;such\;that\;A+2X=2B+C\;\lbrack2013\rbrack\\}$

Step-by-step Explanation:

$\style{font-size:14px}{A+2X=2B+C\\\Rightarrow2X=2B+C-A\\2X=2\begin{bmatrix}-3&2\\4&0\end{bmatrix}+\begin{bmatrix}4&0\\0&2\end{bmatrix}-\begin{bmatrix}2&-6\\2&0\end{bmatrix}\\2X=\begin{bmatrix}-6&4\\8&0\end{bmatrix}+\begin{bmatrix}4&0\\0&2\end{bmatrix}-\begin{bmatrix}2&-6\\2&0\end{bmatrix}\\2X=\begin{bmatrix}-6+4-2&4+0+6\\8+0-2&0+2-0\end{bmatrix}\\2X=\begin{bmatrix}-4&10\\6&2\end{bmatrix}\\X=\frac12\begin{bmatrix}-4&10\\6&2\end{bmatrix}\\\boldsymbol X\boldsymbol=\mathbf{\left[\begin{array}{cc}-2&5\\3&1\end{array}\right]}\\}$

$\style{font-size:14px}{21.\;Find\;x\;and\;y\;if\;\begin{bmatrix}x&3x\\y&4y\end{bmatrix}\begin{bmatrix}2\\1\end{bmatrix}=\begin{bmatrix}5\\12\end{bmatrix}.\;\lbrack2013\rbrack\\}$

Solution: x = 1, y = 2 .

Step-by-step Explanation:

$\style{font-size:14px}{\begin{bmatrix}x&3x\\y&4y\end{bmatrix}\begin{bmatrix}2\\1\end{bmatrix}=\begin{bmatrix}5\\12\end{bmatrix}\\\begin{bmatrix}x\times2+3x\times1\\y\times2+4y\times1\end{bmatrix}=\begin{bmatrix}5\\12\end{bmatrix}\\\begin{bmatrix}5x\\6y\end{bmatrix}=\begin{bmatrix}5\\12\end{bmatrix}\\5x=5\;and\;6y=12\\\boldsymbol x\boldsymbol=\mathbf1\boldsymbol\;\boldsymbol a\boldsymbol n\boldsymbol d\boldsymbol\;\boldsymbol y\boldsymbol=\mathbf2}$

$\style{font-size:14px}{22.\;If\;A=\begin{bmatrix}3&1\\-1&2\end{bmatrix}\;and\;I=\begin{bmatrix}1&0\\0&1\end{bmatrix},\\Find\;A^2-5A+7I.\;\;\lbrack2012\rbrack\\}$

Step-by-step Explanation:

$\style{font-size:14px}{A^2-5A+7I\\A^2=\begin{bmatrix}3&1\\-1&2\end{bmatrix}\begin{bmatrix}3&1\\-1&2\end{bmatrix}\\=\begin{bmatrix}3\times3+1(-1)&3\times1+1\times2\\(-1)\times3+2(-1)&(-1)\times1+2\times2\end{bmatrix}\\=\begin{bmatrix}8&5\\-5&3\end{bmatrix}\\A^2-5A+7I\\=\begin{bmatrix}8&5\\-5&3\end{bmatrix}-5\begin{bmatrix}3&1\\-1&2\end{bmatrix}+7\begin{bmatrix}1&0\\0&1\end{bmatrix}\\=\begin{bmatrix}8&5\\-5&3\end{bmatrix}-\begin{bmatrix}15&5\\-5&10\end{bmatrix}+\begin{bmatrix}7&0\\0&7\end{bmatrix}\\=\begin{bmatrix}8-15+7&5-5+0\\-5+5+0&3-10+7\end{bmatrix}\\=\mathbf{\left[\begin{array}{cc}0&0\\0&0\end{array}\right]}\\}$

$\style{font-size:14px}{23.\;Given,\begin{bmatrix}2&1\\-3&4\end{bmatrix}X=\begin{bmatrix}7\\6\end{bmatrix}.\;Write\\(i)\;The\;order\;of\;matrix\;X.\\(ii)\;Matrix\;X.\;\;\;\lbrack2012\rbrack\\\\}$

Step-by-step Explanation:

$\style{font-size:14px}{(i)\;(m\times n)(n\times p)=(m\times p)\\(2\times2)(n\times p)=(2\times1)\\\Rightarrow order\;of\;matrix\;X=(2\times1)\\(ii)\;Let\;X=\begin{bmatrix}a\\b\end{bmatrix}\\\begin{bmatrix}2&1\\-3&4\end{bmatrix}\begin{bmatrix}a\\b\end{bmatrix}=\begin{bmatrix}7\\6\end{bmatrix}\\\\\begin{bmatrix}2a+b\\-3a+4b\end{bmatrix}=\begin{bmatrix}7\\6\end{bmatrix}\\2a+b=7\;…(1)\\-3a+4b=6\;…(2)\\Multiplying\;(1)\;by\;3\;and\;(2)\;by\;2\;and\;adding,\\\begin{array}{r}6a+3b=21\\+-6a+8b=12\\\hline11b=33\end{array}\\b=3\\Putting\;b=3\;in\;(1)\\2a+3=7\\2a=4\\a=2\\\boldsymbol M\boldsymbol a\boldsymbol t\boldsymbol r\boldsymbol i\boldsymbol x\boldsymbol\;\boldsymbol X\boldsymbol=\mathbf{\left[\begin{array}{c}2\\3\end{array}\right]}\\\\}$

$24.\;If\;A=\begin{bmatrix}3&5\\4&-2\end{bmatrix}and\;B=\begin{bmatrix}2\\4\end{bmatrix}\\is\;the\;product\;AB\;possible?\;Give\;a\;reason.\\If\;yes,\;find\;AB.\;\;\lbrack2011\rbrack$

Step-by-step Explanation:

$\\Order\;of\;1st\;matrix\;A=(2\times2)\\order\;of\;2nd\;matrix\;B=(2\times1)\\Product\;AB\;is\;possible\;if\\No.\;of\;columns\;in\;matrix\;A=No.\;of\;rows\;in\;matrix\;B\\Here,\;AB\;is\;possible.\\AB=\begin{bmatrix}3&5\\4&-2\end{bmatrix}\begin{bmatrix}2\\4\end{bmatrix}\\=\begin{bmatrix}3\times2+5\times4\\4\times2+(-2)\times4\end{bmatrix}\\=\mathbf{\left[\begin{array}{c}26\\0\end{array}\right]}$

$25.\;If\;A=\begin{bmatrix}2&5\\1&3\end{bmatrix},\;B=\begin{bmatrix}4&-2\\-1&3\end{bmatrix}\;and\\I\;is\;the\;identity\;matrix\;of\;same\;order\;and\\A^t\;is\;the\;transpose\;of\;matrix\;A,\;\\Find\;A^t.B+BI\;\;\;\lbrack2011\rbrack\\$

Step-by-step Explanation:

$\style{font-size:14px}{A=\begin{bmatrix}2&5\\1&3\end{bmatrix}\\Transpose\;of\;a\;matrix\;is\;found\;by\;interchanging\;rows\;and\;columns.\\\therefore A^t=\begin{bmatrix}2&1\\5&3\end{bmatrix}\\Now,\;A^t.B+BI\;\;\\=\begin{bmatrix}2&1\\5&3\end{bmatrix}\begin{bmatrix}4&-2\\-1&3\end{bmatrix}+\begin{bmatrix}4&-2\\-1&3\end{bmatrix}\begin{bmatrix}1&0\\0&1\end{bmatrix}\\=\begin{bmatrix}2\times4+1(-1)&2(-2)+1\times3\\5\times4+3(-1)&5(-2)+3\times3\end{bmatrix}+\begin{bmatrix}4\times1+(-2)0&4\times0+(-2)1\\(-1)1+3\times0&(-1)0+3\times1\end{bmatrix}\\=\begin{bmatrix}7&-1\\17&-1\end{bmatrix}+\begin{bmatrix}4&-2\\-1&3\end{bmatrix}\\=\begin{bmatrix}7+4&-1-2\\17-1&-1+3\end{bmatrix}\\=\mathbf{\left[\begin{array}{cc}21&-3\\16&2\end{array}\right]}}$

$\style{font-size:14px}{26.\;Given\;A=\begin{bmatrix}3&-2\\-1&4\end{bmatrix},\;B=\begin{bmatrix}6\\1\end{bmatrix},\;C=\begin{bmatrix}-4\\5\end{bmatrix},\;D=\begin{bmatrix}2\\2\end{bmatrix}\\Find\;AB+2C-4D.\;\;\lbrack2010\rbrack}$

Step-by-step Explanation:

$\style{font-size:14px}{AB+2C-4D\\\begin{bmatrix}3&-2\\-1&4\end{bmatrix}\begin{bmatrix}6\\1\end{bmatrix}+2\begin{bmatrix}-4\\5\end{bmatrix}-4\begin{bmatrix}2\\2\end{bmatrix}\\\begin{bmatrix}3\times6+(-2)1\\(-1)6+4\times1\end{bmatrix}+\begin{bmatrix}-8\\10\end{bmatrix}-\begin{bmatrix}8\\8\end{bmatrix}\\\begin{bmatrix}16\\-2\end{bmatrix}+\begin{bmatrix}-8\\10\end{bmatrix}-\begin{bmatrix}8\\8\end{bmatrix}\\\begin{bmatrix}16-8-8\\-2+10-8\end{bmatrix}\\\mathbf{\left[\begin{array}{c}0\\0\end{array}\right]}\\}$

$\style{font-size:14px}{27.\;Evaluate:\\\begin{bmatrix}4\sin30^\circ&2\cos60^\circ\\\sin90^\circ&2\cos0^\circ\end{bmatrix}\begin{bmatrix}4&5\\5&4\end{bmatrix}\;\;\lbrack2010\rbrack\\}$

Step-by-step Explanation:

$\style{font-size:14px}{\begin{bmatrix}4\sin30^\circ&2\cos60^\circ\\\sin90^\circ&2\cos0^\circ\end{bmatrix}\begin{bmatrix}4&5\\5&4\end{bmatrix}\;\\\begin{bmatrix}4\times\frac12&2\times\frac12\\1&2\times1\end{bmatrix}\begin{bmatrix}4&5\\5&4\end{bmatrix}\;\\\begin{bmatrix}2&1\\1&2\end{bmatrix}\begin{bmatrix}4&5\\5&4\end{bmatrix}\;\\\begin{bmatrix}2\times4+1\times5&2\times5+1\times4\\1\times4+2\times5&1\times5+2\times4\end{bmatrix}\;\\\mathbf{\left[\begin{array}{cc}13&14\\14&13\end{array}\right]}\boldsymbol\;\\}$

Subscribe to my YouTube channel for more such educational content.

Sharing is caring!